Differential vasomotor effects of insulin on gastrocnemius and soleus feed arteries in the OLETF rat model: role of endothelin‐1. Issue 1 (25th October 2013) - Jenkins, Nathan T.; Padilla, Jaume; Martin, Jeffrey S.; Crissey, Jacqueline M.; Thyfault, John P.; Rector, R. Scott; Laughlin, M. Harold
New findings What is the central question of this study? This study investigated the influence of obesity on insulin‐induced vasomotor reactivity in rat skeletal muscle feed arteries. What is the main finding and its importance? Irrespective of obesity, the gastrocnemius feed artery displayed diminished insulin‐induced vasodilatory response compared to the soleus feed artery. This difference between the arteries was abolished in the presence of an endothelin‐1 receptor antagonist. Therefore, our findings demonstrate that insulin‐induced endothelin‐1 production is not uniform among all skeletal muscle resistance vessels. The vascular actions of insulin are complex, because it can stimulate both nitric oxide‐mediated dilatation and endothelin (ET)‐1‐mediated constriction. We examined vasoreactivity to insulin in isolated feed arteries of the gastrocnemius (GFA) and soleus muscles (SFA) of 32‐week‐old Long–Evans Tokushima Otsuka (LETO) and Otsuka Long–Evans Tokushima fatty (OLETF) rats, a hyperphagic rodent model of obesity and insulin resistance. The insulin‐induced vasoreactivity of SFA and GFA was similar in LETO (healthy) and OLETF (obese/insulin‐resistant) rats. However, examination of between‐vessel effects revealed a number of novel insights into the heterogeneous vascular effects of insulin. Soleus feed arteries dilated more than GFA in LETO at 100 and 1000 μIU ml−1 insulin (23 versus 6 and 28 versus 0%, respectively; P < 0.05 for between‐vessel differences). Likewise, in OLETF rats there was significantly greater dilatation in SFA than GFA at 10, 100 and 1000 μIU ml−1 insulin (28 versus 3, 30 versus 0 and 34 versus 0%, respectively; all P < 0.05). In the presence of 3 μm tezosentan, a non‐specific endothelin‐1 receptor blocker, insulin‐induced dilatation of the GFA was enhanced such that differences between vessels were largely abolished in both groups. Furthermore, acetylecholine‐induced dilatation was significantly greater in SFA than GFA within each group, whereas sodium nitroprusside‐induced dilatory responses were greater in the GFA compared with the SFA. Overall, our findings indicate that the insulin/endothelin‐1 vasoconstrictor pathway is more active in GFA than in SFA, independent of obesity in the OLETF rat model.